ESTUDIO DE EFICACIA DE UN PROGRAMA DE MEJORA EN EL MANEJO DEL HOSTIGAMIENTO ENTRE PARES (BULLYING) EN EL ÁMBITO ÁULICO EN DOCENTES DE NIVEL PRIMARIO DE LA CIUDAD DE BUENOS AIRES. ESTUDIO DE LAS CREENCIAS DE LOS DOCENTES SOBRE LOS FACTORES CAUSALES Y ACCIO - Bernardo Kerman (European Scientific Journal, ESJ, 2015)
The effectiveness of a program to improve the management of violence is evaluated specifically in terms of enlightenment and awareness of causal and preventive factors of peer harassment, and bullying in schools in Buenos Aires City. It is considered that the attitude of teachers in relation to episodes of harassment in pairs, depends on the beliefs that they have about causal and preventive factors. Therefore, this study is a critical study. The design is to participate in a workshop of six meetings for half an hour each, in which different training devices and techniques will be developed to modify the beliefs and to indirectly improve the management of violence by teachers. However, this study will be compared with a control group.